![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x/3 - 1/2 = 1/5
<=> x/3 = 1/5 + 1/2
<=> x/3 = 7/10
<=> 10x = 3 . 7
<=> 10x = 21
<=> x = 21 : 10
<=> x = 2,1
Vậy x = 2,1
b) x/5 + 1/2 = 6/10
<=> x/5 = 6/10 - 1/2
<=> x/5 = 6/10 - 5/10
<=> x/5 = 1/10
<=> 10x = 5
<=> x = 5 : 10
<=> x = 0,5
Vậy x = 0,5
c) x + 3/15 = 1/3
<=> x = 1/3 - 3/15
<=> x = 5/15 - 3/15
<=> x = 2/15
Vậy x = 2/15
d) x - 14/4 = 1/4
<=> x = 1/4 + 14/4
<=> x = 15/4
Vậy x = 15/4
![](https://rs.olm.vn/images/avt/0.png?1311)
1) x - 2 = -6
x = -6 + 2
x = -4
2) -5 . x - ( -3 ) =13
-5 . x = 13 + ( -3 )
-5 . x = 10
x = 10 : ( -5 )
x = -2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,\frac{2}{3}+\frac{4}{9}+\frac{1}{5}+\frac{2}{15}+\frac{3}{2}-\frac{17}{18}\)
\(< =>\frac{4}{9}+\frac{3}{2}+\left(\frac{2}{3}+\frac{1}{5}+\frac{2}{15}\right)-\frac{17}{18}\)
\(< =>\frac{8}{18}+\frac{27}{18}+\left(\frac{10}{15}+\frac{3}{15}+\frac{2}{15}\right)-\frac{17}{18}\)
\(< =>\frac{35}{18}+1-\frac{17}{18}\)
\(< =>\frac{53}{18}-\frac{17}{18}\)
\(< =>2\)
\(2,\frac{13}{28}\cdot\frac{5}{12}-\frac{5}{28}\cdot\frac{1}{12}\)
\(< =>\left(\frac{13}{28}-\frac{5}{28}\right)\cdot\left(\frac{5}{12}-\frac{1}{12}\right)\)
\(< =>\frac{2}{7}\cdot\frac{1}{3}\)
\(< =>\frac{2}{21}\)
\(3,\frac{19}{4}\cdot\frac{15}{23}-\frac{15}{4}\cdot\frac{7}{23}+\frac{15}{4}\cdot\frac{11}{23}\)
\(< =>\frac{285}{92}-\frac{105}{92}+\frac{165}{92}\)
\(< =>\frac{15}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{8}{9}\) : ( 2 - 3 \(\times\) y) = \(\dfrac{5}{3}\)
2 - 3 \(\times\) y = \(\dfrac{8}{9}\) : \(\dfrac{5}{3}\)
2 - 3 \(\times\) y = \(\dfrac{8}{15}\)
3 \(\times\) y = 2 - \(\dfrac{8}{15}\)
3 \(\times\) y = \(\dfrac{22}{15}\)
y = \(\dfrac{22}{15}\) : 3
y = \(\dfrac{22}{45}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x+\frac{5}{3}\right)\left(x-\frac{5}{4}\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}\left(x+\frac{5}{3}\right)=0\\\left(x-\frac{5}{4}\right)=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-\frac{5}{3}\\x=\frac{5}{4}\end{cases}}}\)
\(\frac{1}{3}+\frac{1}{2}\div x=-4\)
\(\frac{1}{2}\div x=-4-\frac{1}{3}\)
\(\frac{1}{2}\div x=-\frac{13}{3}\)
\(x=-\frac{3}{26}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{3}{x+5}=15\%\)
\(\frac{3}{x+5}=\frac{3}{20}\)
\(\Rightarrow x+5=20\Rightarrow x=15\)
1/2-(2/3×x-1/3)=2/3
(2/3×x-1/3)=1/2-1/3
(2/3×x-1/3)=1/6
2/3×x=1/6+1/3
2/3×x=1/2
x=1/2:2/3
x=3/4
vậy x=3/4
3/x+5=15%
3/x+5=3/20
3/x=3/20-5
3/x=-97/20
3×20=x×-97
60=x×-97
x×-97=60
x=60:-97
x=-60/97
vậy x=-60/97
Ta có:\(\frac{1}{2}-\left(\frac{2}{3}\times x-\frac{1}{3}\right)=\frac{2}{3}\Rightarrow\frac{2}{3}\times x-\frac{1}{3}=\frac{1}{2}-\frac{2}{3}\)
\(\Rightarrow\frac{2}{3}\times x-\frac{1}{3}=\frac{-1}{6}\)
\(\Rightarrow\frac{2}{3}\times x=\frac{-1}{6}+\frac{1}{3}\Rightarrow\frac{2}{3}\times x=\frac{1}{6}\Rightarrow x=\frac{1}{6}:\frac{2}{3}=\frac{1}{4}\)
Vậy x=1/4
Ta có:\(\frac{3}{x}+5=15\%\Rightarrow\frac{3}{x}=\frac{3}{20}-5\Rightarrow\frac{3}{x}=\frac{-97}{20}\Rightarrow x=\frac{3}{\frac{-97}{20}}=\frac{-60}{97}\)
Vậy x=-60/97